Identification of a Novel Human Rho Protein with Unusual Properties: GTPase Deficiency and In Vivo Farnesylation - Rosemary Foster; Kang‐Quan Hu; Yu Lu; Katherine M. Nolan; Julia Thissen; Jeffrey Settleman (1996)
We have identified a human Rho protein, RhoE, which has unusual structural and biochemical properties that suggest a novel mechanism of regulation. Within a region that is highly conserved among small GTPases, RhoE contains amino acid differences specifically at three positions that confer oncogenicity to Ras (12, 59, and 61). As predicted by these substitutions, which impair GTP hydrolysis in Ras, RhoE binds GTP but lacks intrinsic GTPase activity and is resistant to Rho-specific GTPase-activating proteins. Replacing all three positions in RhoE with conventional amino acids completely restores GTPase activity. In vivo, RhoE is found exclusively in the GTP-bound form, suggesting that unlike previously characterized small GTPases, RhoE may be normally maintained in an activated state. Thus, amino acid changes in Ras that are selected during tumorigenesis have evolved naturally in this Rho protein and have similar consequences for catalytic function. All previously described Rho family proteins are modified by geranylgeranylation, a lipid attachment required for proper membrane localization. In contrast, the carboxy-terminal sequence of RhoE predicts that, like Ras proteins, RhoE is normally farnesylated. Indeed, we have found that RhoE in farnesylated in vivo and that this modification is required for association with the plasma membrane and with an unidentified cellular structure that may play a role in adhesion. Thus, two unusual structural features of this novel Rho protein suggest a striking evolutionary divergence from the Rho family of GTPases.